2020
DOI: 10.3389/fpsyt.2020.00704
|View full text |Cite
|
Sign up to set email alerts
|

The Innate Immune System and Inflammatory Priming: Potential Mechanistic Factors in Mood Disorders and Gulf War Illness

Abstract: Gulf War Illness is a chronic multisystem disorder affecting approximately a third of the Veterans of the Gulf War, manifesting with physical and mental health symptoms such as cognitive impairment, neurological abnormalities, and dysregulation of mood. Among the leading theories into the etiology of this multisystem disorder is environmental exposure to the various neurotoxins encountered in the Gulf Theatre, including organophosphates, nerve agents, pyridostigmine bromide, smoke from oil well fires, and depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 113 publications
(128 reference statements)
0
14
0
Order By: Relevance
“…Amongst all of the generated networks, two cytokines, tumor necrosis factor (TNF) and interferon gamma (IFN-g), a kinase, PDPK1, and a phosphatase, PTEN, were observed across all of the time points and exposures (Tables 4 , 5 , and 6 ). Therefore, these time-independent common nodes are highly connected to the dataset, and may be shared links to the observed neuroinflammation with both of these AChEIs [ 2 , 19 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Amongst all of the generated networks, two cytokines, tumor necrosis factor (TNF) and interferon gamma (IFN-g), a kinase, PDPK1, and a phosphatase, PTEN, were observed across all of the time points and exposures (Tables 4 , 5 , and 6 ). Therefore, these time-independent common nodes are highly connected to the dataset, and may be shared links to the observed neuroinflammation with both of these AChEIs [ 2 , 19 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of a chronic inflammatory response has been reported in studies on GW veteran cohorts, where blood samples are taken and analyzed for biomarkers of inflammation. These studies have reported dysregulation of immune cells and other inflammatory markers such as C-reactive protein, Tau proteins, complement proteins, cytokines and chemokines [13,[65][66][67]. This may in part explain why patients with GWI report multiorgan disorders whose causes are difficult to pinpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of the previously mentioned two functional statuses called the resting and activation statuses, microglia are now believed to be in a continuum status, ranging from resting state to full activation. The concepts of “microglia priming” have been proposed to explain the exaggerated immune responses when microglia receive a second insult [ 40 , 41 , 42 , 43 ]. In prime status, microglia could not be differentiated from the resting state by morphological analysis or even at transcriptional levels.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies indicated that ELS could prime microglia, leading to exaggerated microglial immune responses in later life, which is responsible for various neurological disorders. The concepts of “microglia priming” and the “two-hit hypothesis” have guided work in the field of neuroimmunology over the last decade [ 40 , 41 , 42 , 43 ]. Microglia are highly plastic and could be pre-activated or ‘primed’ by an earlier inflammatory event, which leads to amplified responses to a second inflammatory insult, that is, “innate immune memory (IIM).” Our data indicated that NLRP3 signaling priming and activation was responsible for microglia priming and activation and bridged the linkage between ELS and drug addiction.…”
Section: Discussionmentioning
confidence: 99%